PASAR SEBAGAI RUANG SEDULURAN MASYARAKAT JAWA - Endy Marlina; Arya Ronald; Sudaryono Sudaryono; Atyanto Dharoko (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2015)
This study found the concept of “market as seduluran (brotherhood) space”, Javanese local wisdom in managing social interactions. The concept of social harmony is the realization of Javanese local wisdom that has existed and still running today. In-depth exploration reveals empirical themes that show strategies of market management. This strategy illustrates the public perception of the market, they are market as a common space, space of dhasaran, familial spaces, social media expansion, socioeconomic space, space of paseduluran (brotherhood), chatrooms and entertainment space, changes of the management of market space, the openness of market space, and network of information, knowledge, and culture. Another finding is the task of the market as physical control, functional frame, social milieu, and cultural symbolization. The themes which were found then were further explored with eiditic depth and managed to find a concept of seduluran as the basis of public understanding of the market. The concept of seduluran underlying strategies to maintain social harmony of the society. This concept managed to keep the existence of markets as traditional economic space in the development of a modern economy.